Organoids of epithelial ovarian cancer as an emerging preclinical in vitro tool: a review - Sander Dumont; Ziga Jan; Ruben Heremans; Toon Van Gorp; Ignace Vergote; Dirk Timmerman (BMC, 2019)
Abstract Epithelial ovarian cancer (EOC) remains the most lethal gynecological cancer in developed countries, indicating the need for further research. Although current cancer models prove useful, they have major limitations. Organoids, a novel in vitro 3D cell culture technique, derived from stem cells, could provide a bridge between the current preclinical platforms. However, this technique is still in its early stages. After conducting a systematic literature search, only sixteen manuscripts concerning ovarian related organoids could be retrieved. In this review, we discuss current tumor models, including organoids and provide a comprehensive review about organoids of ovarian tissue. Potential future applications are addressed, proving organoids to be an interesting platform for modeling tumorigenesis, drug testing and screening and other applications. Recent advancements could usher in a new era of highly personalized medicine in EOC.